(untitled) (Fiep Bulletin - online, 2013)
The problem of research that leads this work was: Does Urinary Incontinence influence quality of life of women over fiftyfive years old? The general purpose from looking for answers was to find out the incidence and the impact of Urinary Incontinence in women with age equal or above fifty-five years. Exploratory research was realized to apply a questionnaire (ICIQ- SF) about the conditions of life and health and how the problems of Urinary Incontinence influence the life of these women. As the result from this work, among 108 women, 92 of them complained of their momentaneous quality of life. At this research, the Urinary Incontinence is a serious problem of public health in our country and, without doubts, affects the quality of life of people with this patology.